Novel methodology to perform sulfur hexafluoride (SF6)-based multiple-breath wash-in and washout in infants using current commercially available equipment - Gustafsson, P M; Robinson, P D; Lindblad, A; Oberli, D (Journal of applied physiology (1985), 2016)
Multiple-breath inert gas washout (MBW) is ideally suited for early detection and monitoring of serious lung disease, such as cystic fibrosis, in infants and young children. Validated commercial options for the MBW technique are limited, and suitability of nitrogen (N )-based MBW is of concern given the detrimental effect of exposure to pure O on infant breathing pattern. We propose novel methodology using commercially available N MBW equipment to facilitate 4% sulfur hexafluoride (SF ) multiple-breath inert gas wash-in and washout suitable for the infant age range. CO , O , and sidestream molar mass sensor signals were used to accurately calculate SF concentrations. An improved dynamic method for synchronization of gas and respiratory flow was developed to take into account variations in sidestream sample flow during MBW measurement. In vitro validation of triplicate functional residual capacity (FRC) assessments was undertaken under dry ambient conditions using lung models ranging from 90 to 267 ml, with tidal volumes of 28-79 ml, and respiratory rates 20-60 per minute. The relative mean (SD, 95% confidence interval) error of triplicate FRC determinations by washout was -0.26 (1.84, -3.86 to +3.35)% and by wash-in was 0.57 (2.66, -4.66 to +5.79)%. The standard deviations [mean (SD)] of percentage error among FRC triplicates were 1.40 (1.14) and 1.38 (1.32) for washout and wash-in, respectively. The novel methodology presented achieved FRC accuracy as outlined by current MBW consensus recommendations (95% of measurements within 5% accuracy). Further clinical evaluation is required, but this new technique, using existing commercially available equipment, has exciting potential for research and clinical use.